2017
DOI: 10.1149/2.0011804jes
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical UV Sensor Using Carbon Quantum Dot/Graphene Semiconductor

Abstract: Our group has developed an electrochemical UV sensor utilizing carbon quantum dots as the photoactive material functionalizing a graphene semiconductor layer. When used as a photoactive electrode in contact with a solid polymer electrolyte in a photoelectrochemical cell, illumination under UV radiation at 365 nm induces a photocurrent with a corresponding change in device voltage. The time-dependent change in voltage is a function of UV radiation intensity. Varying the UV LED power density from 26.6 mW/cm 2 (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 47 publications
(64 reference statements)
0
7
0
Order By: Relevance
“…Additionally, they are often used for signal amplification by serving as nanocarriers including electron transfer promoters, nanozymes, detector bioreceptors, electroactive labeling elements, and catalysts [34][35][36][37], hence offering novel strategies for biosensing platforms and their practical applicability. Over the last decade, numerous nanomaterials have been continuously studied and employed as signal-amplifying species such as nanoparticles (NPs) [38][39][40], graphene [41][42][43], nanowires [44], carbon nanotubes (CNTs) [45], magnetic beads [46,47] and quantum dots (QDs) [48,49]. Among these nanomaterials, QDs such as graphene quantum dots (GQDs) and carbon dots (CDs) are becoming quite well-known for their multifarious properties such as signal amplifying characteristics, good biocompatibility, tunable size, electro-catalytic performance as well as their capacity for the concurrent and multiple detection of biomolecules.…”
Section: Role Of Nanomaterials In Biosensingmentioning
confidence: 99%
“…Additionally, they are often used for signal amplification by serving as nanocarriers including electron transfer promoters, nanozymes, detector bioreceptors, electroactive labeling elements, and catalysts [34][35][36][37], hence offering novel strategies for biosensing platforms and their practical applicability. Over the last decade, numerous nanomaterials have been continuously studied and employed as signal-amplifying species such as nanoparticles (NPs) [38][39][40], graphene [41][42][43], nanowires [44], carbon nanotubes (CNTs) [45], magnetic beads [46,47] and quantum dots (QDs) [48,49]. Among these nanomaterials, QDs such as graphene quantum dots (GQDs) and carbon dots (CDs) are becoming quite well-known for their multifarious properties such as signal amplifying characteristics, good biocompatibility, tunable size, electro-catalytic performance as well as their capacity for the concurrent and multiple detection of biomolecules.…”
Section: Role Of Nanomaterials In Biosensingmentioning
confidence: 99%
“…CDs or graphene quantum dots are zero-dimensional carbon nanomaterials. 63,64 Considerable attention has been paid to fluorescent CDs or graphene quantum dots owing to their small sizes (∼5 nm), low toxicity, good biocompatibility, stable photoluminescence and chemical inertness, which are advantageous over other fluorescence probes used for intracellular sensors. 20,65 In the application of intracellular sensor, CDs generally enter living cells by incubating living cells with CDs at 37 °C and then intracellular microenvironment (e.g., pH value and temperatures) or intracellular molecules or ions are analyzed by CDs through confocal fluorescence microscopic technique or electrochemistry methods.…”
Section: Carbon Nanomaterials and Their Possibility As Intracellular ...mentioning
confidence: 99%
“…However, if one wants to extend their field of application to optoelectronic devices, it is necessary to study CDs/graphene composites in the solid phase and to evaluate their interaction with target substrates. Recently, N-doped carbon quantum dots/graphene material was used as a photoactive electrode for UV sensing in an electrochemical cell . Chen et al demonstrated that adding carbon quantum dots to graphene improved the photoresponsivity of a graphene/silicon Schottky junction photodetector.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, N-doped carbon quantum dots/graphene material was used as a photoactive electrode for UV sensing in an electrochemical cell. 42 Chen et al 43 demonstrated that adding carbon quantum dots to graphene improved the photoresponsivity of a graphene/silicon Schottky junction photodetector. Moreover, films composed of quantum dots of different materials (CsPbI 3 ) and micrometer-sized graphene sheets were successfully used to improve the efficiency and stability of allinorganic perovskite solar cells.…”
Section: Introductionmentioning
confidence: 99%